Study on biological activity of tissues from bivalve mollusks - E. P. Karaulova; H. D. Yoon; J. G. Kim; S. H. Park; T. N. Slutskaya; E. V. Yakush (Известия ТИНРО, 2018)
Biological activity of tissues and enzyme hydrolyzates is investigated for three species of bivalve mollusks: Corbicula japonica, Mercenaria mercenaria, and Anadara broughtonii. Antiradical activity of all samples has increased signifcantly during their enzymatic hydrolysis: in eight times for C. japonica, in three times for M. mercenaria, and in 2.5 times for A. broughtonii. The highest anti-trombolitic activity (0.0823 units) is found for the hydrolyzate of C. japonica in concentration of 10 mg/mL. Angiotensin I-converting enzyme inhibitory activity is found only for the hydrolyzate of M. mercenaria in concentration of 10–100 mg/mL. The maximum inhibitory activity for alpha-amylase and alpha-glycosidase (7.5 and 7.2 %, respectively) is observed for the hydrolyzate of M. mercenaria in concentration 1 mg/mL. Hepatoprotective activity, measured by survival rate of HepG2 hepatocytes, is detected for the hydrolyzate of tissues for all species in weak concentrations: 0.1 mg/mL for C. japonica and M. mercenaria and 0.2 mg/mL for A. broughtonii.